Size Dependent Elastic and Thermophysical Properties of Zinc Oxide Nanowires. Issue 3 (1st July 2019) - Tripathi, Sudhanshu; Agarwal, Rekha; Singh, Devraj
Size dependent characterisation is important for applications in nanoelectromechanical systems (NEMS), nanogenerators, biosensors and other related areas at higher temperature regimes. In this paper we have computed elastic, mechanical, thermal and ultrasonic properties of zinc oxide nanowires (ZnO-NWs) of different diameters at high temperatures. The higher order elastic constants of ZnO-NWs were computed using a simple interaction potential model. The mechanical properties such as bulk modulus, Young's modulus, shear modulus and Poisson's ratio were determined based on the formulated elastic constants. Various ultrasonic parameters such as ultrasonic wave velocities, ultrasonic Grüneisen parameter and ultrasonic attenuation were obtained with the help of elastic constants and density. The temperature dependent ultrasonic wave velocities propagating along the length of the nanowire at different orientations were calculated using elastic constants to determine anisotropic behaviour. The diameter dependent ultrasonic losses and thermal characteristics of ZnO-NWs were also determined. The ultrasonic attenuation due to the phonon-viscosity mechanism is predominant for the total ultrasonic attenuation for ZnO-NWs. The correlation among the ultrasonic parameters, thermal conductivity and size of ZnO-NWs is established leading to potential industrial applications.